Performing exile : foreign bodies (2017)
Bringing together a range of perspectives to examine the full impact of political, socioeconomic or psychological experiences of exile, Performing Exile presents an inclusive mix of voices from varied cultural and geographic affiliations. The collected essays in this book focus on live performances that were inspired by living in exile. Chapters blend close critical analysis and ethnography to document and interrogate performances and the contexts that inform them. In a world where exiled populations continue to grow, the role of art to document and engage with these experiences will continue to be essential, and this diverse book offers an important model for understanding the rich body of work being created today. –cFrom publisher's website